Clausewitz and the Personality Characteristics of the Battlefield Commander in British and German Military Doctrine, 1918–1941. (April 2023) - Samuels, Martin
Even after the First World War, the British and German armies remained strongly influenced by Clausewitz, for whom personality rather than mass was the best means to reduce friction. This article explores how this was reflected in their military doctrine between the two world wars. The German regulations showed a clear alignment with Clausewitz's thinking. The British tended to focus on the characteristics Clausewitz had argued were necessary for the troops, rather than for their commanders. The campaigns of 1939/40 caused the Germans to place even greater emphasis on boldness, while the British focused on steadiness and caution.